Seed Mahotsav Scheme for Increasing the Scope of Indigenous Fish Marketing in West Bengal: Perception and Constraint Analysis - Ghosh, Amitava; Sharma, Arpita; Ambulkar, Rashmi (Indian Journal of Marketing, 2013)
Aquaculture is a growing sector with an ability to have a significant impact on the economic development of the country. Out of the total fish production, inland fish production in India contributes 4.930 million metric tonnes, and West Bengal ranks first in the inland fish production in India. Various schemes have been introduced by the Department of Fisheries, West Bengal which have different funding sources,and the recent scheme launched by them is the Seed Mahotsav scheme, which has been started with the objective to conserve indigenous fish species, since there is a growing market demand for them. A study was carried out to review this scheme by studying the beneficiaries’ profile and their perception of satisfaction towards this scheme and the constraints faced in the implementation of the Seed Mahotsav scheme. Rank based quotient method revealed that the scarcity of water in the ponds during the summer months was a major constraint in the successful implementation of this scheme. Based on the findings, a model for effective implementation of the Seed Mahotsav scheme has been suggested, and the paper also provides policy implications of the present research.